1985
DOI: 10.1017/s0376892900034408
|View full text |Cite
|
Sign up to set email alerts
|

Threat to Unique Terrestrial and Marine Environments and Biota in a Japanese National Park

Abstract: Miyake-jima, one of the Izu Islands of southern Japan and a part of the Fuji–Hakone–Izu National Park, has been designated by the governments of Japan and the United States of America as the site for a proposed military airport. Construction of the proposed facility would destroy lands especially designated, by the Environmental Agency of Japan and the Japan Ministry of Agriculture, Forestry, and Fisheries, for special protection. Relocation of farmland and housing from the proposed site would result in destru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Benthic invertebrates such as coral-eating starfish (Moran 1986), prosobranch snails (Moyer et al 1982, 1985, Turner 1992a, and sea urchins (Lessios et al 1984, McClanahan & Kurtis 1991, Glynn & Colgan 1992 frequently exhibit periods of stability punctuated with rapid population increases and decreases. These population changes are frequently associated with major changes in the ecological structure and processes of the coral-reef ecosystem.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Benthic invertebrates such as coral-eating starfish (Moran 1986), prosobranch snails (Moyer et al 1982, 1985, Turner 1992a, and sea urchins (Lessios et al 1984, McClanahan & Kurtis 1991, Glynn & Colgan 1992 frequently exhibit periods of stability punctuated with rapid population increases and decreases. These population changes are frequently associated with major changes in the ecological structure and processes of the coral-reef ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…< l per 10 m2; McClanahan 1990, McClanahan & Muthiga 1992. However, outbreaks or exponential population increases of Drupella snails have been recorded in Japan (Moyer et al 1982(Moyer et al , 1985 in the period 1976 to 1980, Enewetak (Boucher 1986), and in western Australian reefs during the late 1980s until the present (Turner 1992a(Turner , 1994. At high population densities, the snails' scars, left from their feeding on living coral, can kill extensive coral areas leaving reefs to be colonized by filamentous algae.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Habitat selection may be studied at various scales, for example those of physiognomy, landscape, nest site, and foraging site. The scale at which a study is conducted, is an important factor in the interpretation of habitat selection by each species (Cody 1985;Michaels & Cully 1998) (Moyer et al 1985). Three study sites were chosen on the island: Tairoike, Izumisaki and Anegawa.…”
mentioning
confidence: 99%
“…On Miyake-jima, the Izu Islands of Japan, where no native species of carnivorous mammals or snakes were originally present, avian predation seems to be a major mortality factor of the lizard Eumeces okadae. Although extraordinally dense population of E. okadae on Miyakejima (Moyer et al, 1985) suggested that overall predation was low on this island, it seems premature to deny that avian predation is also negligible. During the course of a demographic study of E. okadae conducted during 1978-1984, I had a suspicion that the thrush, Trudus celaenops, very abundant on the island (Higuchi, 1973), was a potential predator on juvenile E. okadae.…”
mentioning
confidence: 99%